Transformation of Public Services in the Island Regions: Improving Community Participation through Information Technology - Yulinda Uang; John Haart Kaloly; Armilla Rumasukun (Universitas Tribhuwana Tunggadewi, 2026)
Transforming public services in archipelagic regions is an urgent need to realize a government that is inclusive, adaptive, and responsive to community needs. Archipelagic regions in Indonesia face unique challenges in providing public services, such as limited infrastructure, geographic barriers, and isolation between regions. These conditions often lead to low service quality and minimal public participation in government processes. This study aims to critically examine how ICT can improve public participation in public services in archipelagic regions, considering geographical challenges and the decentralized conditions of regional government.Using a qualitative approach and case study methods in several archipelagic regions in Indonesia, the findings indicate that digital access and digital literacy are crucial variables influencing the effectiveness of e-government. Infrastructure gaps and low technological capabilities of the community are often the main obstacles. However, when access and literacy are achieved, ICT can open a broad dialogue between citizens and the government, enabling the public to actively participate in the planning, monitoring, and evaluation of public services.Within a decentralized framework, the use of digital social also strengthens the position of local governments as key actors in managing locally-based services. Thus, digital transformation in island regions is not only about system modernization, but also about building a participatory ecosystem based on trust, openness, and connectivity.Transformasi pelayanan publik di wilayah kepulauan merupakan kebutuhan mendesak untuk mewujudkan pemerintahan yang inklusif, adaptif, dan responsif terhadap kebutuhan masyarakat. Wilayah kepulauan di Indonesia menghadapi tantangan unik dalam penyediaan pelayanan publik, seperti keterbatasan infrastruktur, hambatan geografis, dan keterisolasian antarwilayah. Kondisi ini kerap menyebabkan rendahnya kualitas pelayanan serta minimnya partisipasi publik dalam proses pemerintahan. Penelitian ini bertujuan untuk mengkaji secara kritis bagaimana Teknologi Informasi dan Komunikasi (TIK) dapat meningkatkan partisipasi publik dalam pelayanan publik di wilayah kepulauan, dengan mempertimbangkan tantangan geografis dan kondisi desentralisasi pemerintahan daerah. Dengan menggunakan pendekatan kualitatif dan metode studi kasus di beberapa wilayah kepulauan di Indonesia, temuan penelitian menunjukkan bahwa akses digital dan literasi digital merupakan variabel krusial yang memengaruhi efektivitas e-government. Kesenjangan infrastruktur dan rendahnya kapasitas teknologi masyarakat kerap menjadi hambatan utama. Namun, ketika akses dan literasi telah tercapai, TIK mampu membuka ruang dialog yang luas antara warga dan pemerintah, sehingga memungkinkan masyarakat berpartisipasi aktif dalam perencanaan, pemantauan, dan evaluasi pelayanan publik. Dalam kerangka desentralisasi, pemanfaatan media sosial digital juga memperkuat posisi pemerintah daerah sebagai aktor kunci dalam mengelola pelayanan berbasis lokal. Dengan demikian, transformasi digital di wilayah kepulauan tidak hanya berkaitan dengan modernisasi sistem, tetapi juga dengan membangun ekosistem partisipatif yang berlandaskan kepercayaan, keterbukaan, dan konektivitas.